2011
DOI: 10.1016/j.bbr.2011.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Genetic reduction of group 1 metabotropic glutamate receptors alters select behaviors in a mouse model for fragile X syndrome

Abstract: Introduction Genetic heterogeneity likely contributes to variability in the symptoms among individuals with fragile X syndrome (FXS). Studies in the Fmr1 knockout (KO) mouse model for FXS suggest that excessive signaling through group I metabotropic glutamate receptors (Gp1 mGluRs), comprised of subtypes mGluR1 and mGluR5, may play a role. Hence, Gp1 mGluRs may act as modifiers of FXS. Currently no studies have addressed whether manipulation of mGluR1 activity may alter Fmr1 KO behavioral responses, and only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 77 publications
5
43
2
Order By: Relevance
“…Previous studies have shown either a partial or a full rescue of fragile X phenotypes by introducing a heterozygous deletion of the mGlu5 receptor in Fmr1 KO mice (Dolen et al, 2007;Thomas et al, 2011). In the present study, both genetic and pharmacological reductions of mGluR5 function led to a partial rescue of the social tube deficit.…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have shown either a partial or a full rescue of fragile X phenotypes by introducing a heterozygous deletion of the mGlu5 receptor in Fmr1 KO mice (Dolen et al, 2007;Thomas et al, 2011). In the present study, both genetic and pharmacological reductions of mGluR5 function led to a partial rescue of the social tube deficit.…”
Section: Discussionsupporting
confidence: 63%
“…Phenotypes in italics were used to show rescue but the actual defects (e.g., increased vs reduced) varied in different studies. AMPA = α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid; PI3K = phosphoinositide 3-kinase; mTOR = mammalian target of rapamycin; ERK = extracellular regulated kinase; GSK3β = glycogen synthase kinase 3β; LTD = long-term depression; PPI = prepulse inhibition *Most studies show rescue of increased marble burying but at least 2 studies reported decreased burying [118,162]. † These behaviors in rodents are often considered to recapitulate autistic-like behavior in humans.…”
Section: Macro-orchidismmentioning
confidence: 99%
“…• MPEP [43,62,63,97,123,126,128,130,131,134] • MTEP [121] • Fenobam [124,126,133] • AFQ056 [119,125,127,132] CTEP [120,129] mGlu1 Genetic (het) Hyperexcitability: locomotor activity [118] Macro-orchidism, PPI, startle response, AGS, social interaction [118] Pharm Hyperexcitability: AGS (partially) [131] Startle response, rotarod [131] Muscarinic R (subtypes M1 and M4) Genetic (het) Plasticity and hyperexcitability: analgesic response, startle response (M4) [136] PPI, MB, light-dark transition (anxiety), AGS, macro-orchidism [136] Pharm Plasticity and hyperexcitability: AGS (M1+M4) [137,138] Cognition: passive avoidance (M4) [138] Passive avoidance (M1) [137] Group II mGlu N/A GSK3β antagonists used:…”
Section: Macro-orchidismmentioning
confidence: 99%
See 1 more Smart Citation
“…FMR1-deficient mice show increased locomotor activity in the open-field test, elevated anxiety levels in the mirror-chamber test, and impaired social interaction with unfamiliar partners in multiple tests [52][53][54][55][56]. Interestingly, the FXS-like behavior phenotypes in FMR1 KO mice were rescued by repressing the function of group 1 metabotropic glutamate receptors (Gp1 mGluRs).…”
Section: Fragile X Mental Retardationmentioning
confidence: 99%